2022
DOI: 10.3389/frabi.2022.1043302
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in fish and poultry: Public health implications for animal source food production in Nigeria, Egypt, and South Africa

Abstract: Antimicrobial resistance (AMR) is a significant threat to global public health. Specifically, excessive usage of antimicrobials in food animal production is one significant reason for AMR development in humans. Therefore, it is essential to identify the trends of AMR in fish and poultry and develop better surveillance strategies for the future. Despite this imperative need, such information is not well documented, especially in Africa. This study used a systematic review to assess AMR trend, spatial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Finally, because farmers often respond to disease or concern that diseases are spreading locally by using antimicrobials, even non-zoonotic poultry diseases indirectly contribute to antimicrobial resistance in both people and animals [11,12].…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because farmers often respond to disease or concern that diseases are spreading locally by using antimicrobials, even non-zoonotic poultry diseases indirectly contribute to antimicrobial resistance in both people and animals [11,12].…”
Section: Contextmentioning
confidence: 99%
“…Disease may be caused by pathogenic organisms, toxic agents, nutritional deficiencies, metabolic abnormalities, neoplasia, genetic anomalies, or injuries (including predation). Smallholder poultry production in Africa is characterised by high levels of disease, resulting in high mortality that can reach up to 50% in the general population and 75% in brooding chicks (up to the age of 8 weeks) [12][13][14][15][16]. For example, in Ethiopia in 2020, the premature death of 39 million chickens out of a national population of 57 million was reported [17], and a multiyear longitudinal study in Western Kenya showed about 60% of offtake in village chickens is due to mortality from disease [15].…”
Section: The Importance Of Infectious Diseasementioning
confidence: 99%
“…Largely used antibiotics that fish do not effectively metabolize may excrete back into the environment where an estimated 75% of the antibiotic residues (ARs) fed to fish are excreted into the water [ 3 , 4 ]. Nonetheless, the persistence of ARs, under “One Health Continuum” in fish is a global health concern [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of AMR bacteria and associated genes in aquatic products raises food safety concerns, especially since aquatic products are often consumed with minimal cooking or even in their raw state. Resistance genes can subsequently be transferred among bacterial populations in the human intestine, leading to the spread of AMR and potential treatment failure of bacterial infections in humans ( Okon et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%